Peran Akuntan Publik Terhadap Praktek Pelanggaran Prinsip Keterbukaan Yang Berindikasi Pernyataan Menyesatkan (Misleading Statement) Dalam Praktek Di Pasar Modal - Dwi Putri Rezky Sihite; Bismar Nasution; Sunarmi Sunarmi; Mahmul Siregar (Iuris Studia: Jurnal Kajian Hukum, 2021)
A public accountant is a capital market supporting profession whose role is to present quality information in financial reports. Accountants are responsible for providing opinions or expressing fairness in financial statements. In carrying out activities in the capital market, public accountants are obliged to implement the principle of openness because the purpose of the principle of openness is to create an efficient market mechanism. Violations of the transparency principle include misleading statements with mispresentations and omissions in material facts. By providing information based on the principle of transparency, it is possible to anticipate the possibility of not obtaining information or misleading statements to the public or investors. The method used in this paper is normative juridical which uses secondary data and primary data as legal material. Data were collected by conducting a literature study and analyzed qualitatively. The results of this paper are known that public accountants audit financial statements as a professional obligation in the capital market. Public accountants who provide flow services in the capital market must be registered with the Financial Fervices Authority (OJK). Public accountants in providing their assurance services must act professionally and independently. Public accountants always work according to their professional code of ethics, but on the other hand there are errors and fraud in providing assurance services, one of which is misleading statements. Public accountants who make misleading statements are subject to sanctions in the form of administrative, criminal and civil sanctions